Exit strategies for monetary policy - Aleksander Berentsen; Sébastien Kraenzlin; Benjamin Müller (University of Zurich, Department of Economics, 2018)
In response to the financial crisis of 2007/08, all major central banks decreased interest rates to historically low levels and created large excess reserves. Central bankers and academics currently discuss how to implement monetary policy, going forward. We find that paying interest on reserves (IOR) is optimal if the central bank has full fiscal support. If the central bank has no fiscal support, reducing reserves is optimal. This can be achieved by reserve-absorbing operations which hold the size of the balance sheet constant, or by selling assets which reduces the size of the balance sheet.
Keywords: E40; E50; D83; 330; Exit strategies; money market; repo; monetary policy; interest rates